2012
DOI: 10.1371/journal.pgen.1002495
|View full text |Cite
|
Sign up to set email alerts
|

Contrasted Patterns of Molecular Evolution in Dominant and Recessive Self-Incompatibility Haplotypes in Arabidopsis

Abstract: Self-incompatibility has been considered by geneticists a model system for reproductive biology and balancing selection, but our understanding of the genetic basis and evolution of this molecular lock-and-key system has remained limited by the extreme level of sequence divergence among haplotypes, resulting in a lack of appropriate genomic sequences. In this study, we report and analyze the full sequence of eleven distinct haplotypes of the self-incompatibility locus (S-locus) in two closely related Arabidopsi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
131
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 82 publications
(134 citation statements)
references
References 110 publications
3
131
0
Order By: Relevance
“…4c) 14,15 . These Solanaceae SLFs are distributed within 17.9 Mb in tomato and 14.6 Mb in potato, suggesting that the S-loci of the Solanaceae are very large, about two to three orders of magnitude larger than the Brassicaceae S-locus (28-110 kb) 16 .…”
Section: Solanum S-loci Contain Orthologous Slf-like Paralogsmentioning
confidence: 98%
“…4c) 14,15 . These Solanaceae SLFs are distributed within 17.9 Mb in tomato and 14.6 Mb in potato, suggesting that the S-loci of the Solanaceae are very large, about two to three orders of magnitude larger than the Brassicaceae S-locus (28-110 kb) 16 .…”
Section: Solanum S-loci Contain Orthologous Slf-like Paralogsmentioning
confidence: 98%
“…Consistent with theory (Billiard et al, 2007), recessive alleles in diploids have been demonstrated to occur at higher frequency, to show shallower branch lengths in phylogenetic analyses, and more extensive polymorphism within specificities than dominant alleles (Llaurens et al, 2008(Llaurens et al, , 2009Castric et al, 2010;Vekemans et al, 2011;Goubet et al, 2012). In our study, Class B alleles (recessive to A2 and A3 classes) showed lower intraclass polymorphism (13% average pairwise sequence divergence, compared to 25% for Class A2 and 15% for Class A3) but more haplotypes per allele than the two dominant classes (2.56 ± 1.33 compared to 1.59 ± 0.75 in Class A2 and 1.56 ± 0.89 in Class A3, Table 2) and there was high divergence between classes (26-29%; Table 3).…”
Section: Objectives 1 and 2: Diversity And Allele Sharing Of Srk In Dmentioning
confidence: 58%
“…SRK alleles have been grouped into four different dominance classes (A1, A2, A3, B; Prigoda et al, 2005). Polymorphisms within specificities/alleles (which we will refer to as "haplotypes") are more apparent for recessive than dominant alleles because the former are expected to occur at higher frequency and show more sharing between populations (Bechsgaard et al, 2006;Castric and Vekemans, 2007;Castric et al, 2008Castric et al, , 2010Stoeckel et al, 2008;Llaurens et al, 2009;Goubet et al, 2012). There is a single most recessive allele (S1, Class A1; Prigoda et al, 2005) that is found globally and in multiple species in the genus Arabidopsis (Mable et al, 2003;Dart et al, 2004;Prigoda et al, 2005;Mable and Adam, 2007;Castric et al, 2010;Foxe et al, 2010).…”
Section: Notes On Terminology and Known Challenges Associated With Thmentioning
confidence: 99%
See 2 more Smart Citations